Magnetic nozzle performance in a cluster of helicon plasma thrusters - Di Fede, Simone (2024)
A numerical study of the plasma dynamics in a Helicon Plasma Thrusters’ (HPT) cluster is presented. For the first time in the literature, the three-dimensional (3D) plasma dynamics occurring in the plume of a HPTs’ cluster is analyzed. The physical investigation relies on ProPic, a 3D particle-in-cell (PIC) code specifically designed to simulate the plasma dynamics in magnetic nozzles and in a non-axi-symmetric domain. The code has been validated against experiments reported in the literature and cross-validated with Starfish, an open-source two-dimensional PIC software. The physical investigation has revealed an interesting mutual influence between the thrusters that constitute the cluster. Three significant phenomena that affect the cluster’s performance have been identified. The first phenomenon is related to the effect that clustering has on the shape of the magnetic field lines and, in turn, on the divergence angle of the plume. The second phenomenon is related to electron currents flowing among different thrusters, which affect the potential drop across the plume. The third phenomenon is related to the effect that neighboring thrusters have on the plasma potential map and, in turn, on the expansion of the ions.